Use of interactive multimedia technologies for the formation of a common national identity in Cyprus - Παύλου, Μαρίνος (Τμήμα Πολυμέσων και Γραφικών Τεχνών, Σχολή Καλών και Εφαρμοσμένων Τεχνών, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The following thesis explores the "Use of Interactive multimedia technologies as a tool for conflict resolution and peacemaking", through the use of a series of three "Structured Dialogic Design" (SDD) co‐laboratories. During the co‐laboratories participants discussed how these technologies can aid the formation of a common national identity among all Cypriots, regardless of their original ethnic origin. The findings show that the promotion of all the common thinks people of Cyprus share, through all available technologies and the necessary change of people's mind set, can let people of Cyprus hope that the formation of a common national identity and hence reunification of the island is possible.
Keywords: Interactive multimedia technologies; Structured Dialogic Design